Caracterización y variabilidad química de dos aceites esenciales de Croton funckianus [Euphorbiaceae]. (Characterization and Chemical Variability of Two Essential Oils From Croton funckianus [Euphorbiaceae].) - Coy Barrera, C. A.; Gómez, D. C. (Universidad Pedagógica y Tecnológica de Colombia, 2015)
ResumenPara caracterizar químicamente el aceite esencial obtenido tanto de hojas como de frutos de dos muestras de la especie Croton funckianus, colectadas en dos sitios diferentes (Fusagasugá y Bogotá), se realizó el análisis cromatográfico por la técnica de cromatografía de gases acoplada a espectrometría de masas (CG-EM), y posteriormente se compararon los perfiles obtenidos, determinando algunas diferencias para el caso de las hojas y un alto porcentaje de similitudes para el caso de los frutos. El análisis del aceite esencial de hojas de la especie Croton funckianus colectada en Fusagasugá mostró como componentes principales citronelal, 22,8%, neral, 18,6%, carvona, 13,4%, y β-gurjuneno, 12,2%, mientras que para la especie bogotana fueron linalool, 25,8%, α-terpineol, 26,9%, limoneno, 18,9%, y neral, 18,6%. Para el caso de los frutos se observaron diferencias en cuanto al porcentaje de los componentes mayoritarios, para la muestra de Fusagasugá: linalool, 25,0%, borneol, 15,5%, y neral, 18,6%, y para la especie de Bogotá: linalool, 22%, borneol, 13%, y neral, 17,2%.  AbstractA chemical characterization from the essential oil obtained from leaves and fruits of two samples of Croton funckianus that were collected in two dierent sites (Fusagasugá and Bogotá) was conducted. The analysis was performed using gas chromatography coupled with mass spectrometry (GC-MS), and posteriorly, a comparison between the obtained profiles showed some dierences for the leaves and a high percentage of similarity for the fruits. The analysis of the essential oil from the leaves of Croton funckianus collected in Fusagasugá showed as main components citronellal (22.8%), neral (18.6%), carvone (13.4%) and β-gurjunene (12.2%), whereas, for C. funckianus collected in were linalool (25.8%), -terpineol (26.9%), limonene (18.9%) and neral (18.6%). In the fruit samples, dierences in the major components percentages were observed, such that for the Fusagasuga sample were linalool (25.0%), borneol (15.5%) and neral (18.6%), and for the Bogotá sample were linalool (22%), borneol (13%) and neral (17.2%).